Ionic Liquids as Starch Plasticizers: The State of the Art - Susanna Romano; Serena De Santis; Chiara Frezza; Monica Orsini; Giovanni Sotgiu; Marta Feroci; Daniele Rocco (Molecules)
Over the past 15 years, ionic liquids (ILs) have gained increasing attention as potential replacements for traditional organic compounds. Thanks to their remarkable properties, such as non-volatility, chemical stability, low toxicity, solvation power, and the tunability of properties—due to different combinations of cations and anions—ILs are considered ideal in the processing of polymers. Indeed, they have been extensively studied for the dissolution, derivatization, and plasticization of biopolymers to address the growing issue of plastic pollution. The aim of this review is to investigate the recent years’ literature using ILs in starch plasticization. In particular, two major classes of ionic liquids were addressed, the imidazole-based ionic liquids and the choline-derived bioILs. Furthermore, this review aims to provide a comprehensive understanding of the mechanisms behind the interactions between ILs and starch and to study their effect on biopolymer properties.